A Selective α7 Nicotinic Acetylcholine Receptor Agonist, PNU-282987, Attenuates ILC2s Activation and Alternaria-Induced Airway Inflammation - Yuan, Fang; Jiang, Lili; Li, Qianyang; Sokulsky, Leon; Wanyan, Yuanyuan; Wang, Lingli; Liu, Xiaojie; Zhou, Lujia; Tay, Hock L.; Zhang, Guojun; Yang, Ming; Li, Fuguang (Frontiers in Immunology, 2021)
Background: The anti-inflammatory effect of a α7nAChR agonist, PNU-282987, has previously been explored in the context of inflammatory disease, however, the effects of PNU-282987 on type 2 innate lymphoid cells (ILC2s)-mediated allergic airway inflammation has not yet been established. Aims: To determine the effects of PNU-282987 on the function of ILC2s in the context of IL-33- or Alternaria Alternata (AA)-induced airway inflammation. Methods: PNU-282987 was administered to mice that received recombinant IL-33 or AA intranasal challenge. Lung histology and flow cytometry were performed to determine airway inflammation, and the infiltration and activation of ILC2s. The previously published α7nAChR agonist GTS-21 was employed as a comparable reagent. ILC2s were isolated from murine lung tissue and cultured in vitro in the presence of IL-33, IL-2 and IL-7 with/without either PNU-282987 or GTS-21. The expression of the transcription factors GATA3, IKK, and NF-κB was also determined. Results: PNU-282987 and GTS-21 significantly reduced goblet cell hyperplasia in airway, eosinophil infiltration and ILC2s numbers in BALF, following IL-33 or AA challenge. In vitro IL-33 stimulation of isolated lung ILC2s showed a reduction of GATA3 and Ki67 in response to PNU-282987 or GTS-21 treatments. There was a significant reduction in IKK and NF-κB phosphorylation in the PNU-282987 treated group when compared to the GTS-21 treated ILC2s. Conclusion: PNU-282987 inhibits ILC2s-associated airway inflammation, whose effects is comparable to that of GTS-21.